Pengaruh Konten Review Film pada Youtube Cine Crib terhadap Minat Menonton Film di Bioskop - Rohulloh Faturahman; Rosita Anggraini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Cine Crib is a YouTube channel that routinely reviews both international and Indonesian films, with a primary focus on Indonesian cinema. The review content, presented in a relaxed, informative, and entertaining manner, possesses significant potential to influence audience decisions to watch films in cinemas. In the digital era, social media platforms, including YouTube, have emerged as primary information sources that play a vital role in shaping consumer perceptions, preferences, and behaviors concerning movie-watching interest, particularly in theaters. This study aims to determine the influence and the magnitude of the impact of review content on the Cine Crib YouTube channel toward the interest in watching films in cinemas. The research employs a quantitative approach utilizing a survey method. Data were collected by distributing questionnaires to 100 respondents consisting of Cine Crib channel subscribers. Data analysis includes validity and reliability tests, simple linear regression, t-tests, F-tests, and the calculation of the coefficient of determination (R^2). Research findings indicate that film review content on YouTube has a positive and significant influence on the interest in watching films in cinemas, albeit with a weak correlation. Variations in watching interest are influenced by film review content, while the remaining factors are influenced by variables outside the scope of this study. Consequently, the Cine Crib channel represents an effective strategy for increasing interest in cinema-going.